2002
DOI: 10.1212/wnl.59.5.669
|View full text |Cite
|
Sign up to set email alerts
|

Admission glucose level and clinical outcomes in the NINDS rt-PA Stroke Trial

Abstract: In patients with acute ischemic stroke, higher admission glucose levels are associated with significantly lower odds for desirable clinical outcomes and significantly higher odds for symptomatic ICH, regardless of rt-PA treatment. Whether this represents a cause and effect relationship remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
294
5
10

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 469 publications
(331 citation statements)
references
References 45 publications
22
294
5
10
Order By: Relevance
“…Previous studies suggested that a blood glucose level of 160 mg/dL or more may be a cutoff for poor outcomes 20, 24. One study reported a linear relation between admission glucose and an increase in the odds of sICH (OR 1.75 per 100 mg/dL increase in admission glucose) 5. Admission blood glucose levels were identified as a risk factor for sICH after intravenous tPA in several risk models for sICH post‐tPA 11, 25, 26, 27, 28.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that a blood glucose level of 160 mg/dL or more may be a cutoff for poor outcomes 20, 24. One study reported a linear relation between admission glucose and an increase in the odds of sICH (OR 1.75 per 100 mg/dL increase in admission glucose) 5. Admission blood glucose levels were identified as a risk factor for sICH after intravenous tPA in several risk models for sICH post‐tPA 11, 25, 26, 27, 28.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to hyperglycemia, which is considered a poor prognostic factor in stroke patients 3, 4. Increased admission glucose levels in acute stroke have also been associated with longer in‐hospital stay, increased cost, and mortality 5. Hyperglycemia before reperfusion potentially decreases the beneficial effect of tissue‐type plasminogen activator (tPA)6 given that hyperglycemia may act as an inhibitor of fibrinolysis 7…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis of studies examining hyperglycemia in acute ischemic stroke also reported an increase in mortality rate in patients with hyperglycemia at the time of hospital admission [30]. This finding of poor outcomes with hospital admission hyperglycemia was even more strongly correlated between patients who were treated with the thrombolytic tissue plasminogen activator compared to those who were not treated [38].…”
Section: Hyperglycemia In the Stroke Patientmentioning
confidence: 96%
“…44,45 The mechanisms underlying neurologic worsening associated with hyperglycemia are likely multifactorial, and include tissue acidosis, free radical formation, blood-brain barrier disruption, and augmentation of cerebral edema formation. 46 Despite these consistent observations, a definitive study has yet to establish that tight control of glucose improves outcomes. 47 Consensus exists regarding the need to treat hyperglycemia after stroke, and current guidelines recommend a goal glucose concentration of 140 to 180 mg/dL.…”
Section: Glucose Managementmentioning
confidence: 99%